Manufacturing Corporate Life Cycle and Discretionary Accruals with Piecewise Linear Model - Cahyo Indraswono; Anggreni Dian Kurniawati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
This study aimed to investigate the effect of life cycle at the critical point of the growth mature and mature-stagnant stages of discretionary accruals and the effect of company age on discretionary accruals. In addition, this study also examines the differences of discretionary accruals in growth-mature stage and mature-stagnant stage. The data observation in this study is financial statement data of 341 manufacturing companies listed on Indonesia Stock Exchange in 2015-2017. The dependent variable is discretionary accruals that focuses on the piecewise linear model and the independent variables are the life cycle and the company age. Life cycle grouped into two critical point stages, namely the growth-mature stage and the mature-stagnant stage. Multiple linear regression is used to test hypotheses. The results show that there is a negative effect on growth-mature and mature stagnant in critical points of the discretionary accruals and there is a positive effect on the company age on discretionary accruals. Moreover, this study also proves that there are differences in discretionary accruals at growth-mature stage and mature-stagnant stage.